Stojan Bračič, Mateja Petrovčič (Hg.): Partikeln überall. Deutsch – Slowenisch – Chinesich: Ljubljana, Znanstvena založba Filozofske fakultete, 2017, 134 str. - Jesenšek, Vida (Slavia Centralis, 2020)
The article presents the monograph Partikeln überall. Deutsch - Slowenisch - Chinesich, which was published as the 13th volume in the collection of the Slovenian German Studies.